La Expresión Artística en el Desarrollo de las Habilidades Motrices para los niños y niñas de Inicial "2" de la Unidad Educativa Camilo Gallegos Toledo cantón Riobamba Provincia de Chimborazo Parroquia Lizarzaburu, período 2015-2016 - Gaibor Trujillo, Cintya Lisbeth (2016)
The following investigation allowed to know many important aspects of artistic expression in the development of motor skills, this research focuses on finding alternative learning that support the development of motor skills of children mainly that are applied by developing artistic activities ei with music, body development, literature and artistic expression as during this research it has been determined that it is a very suitable method of learning for children of early age. This is why the fundamental basis of this work is the reference framework where the problem was established, the formulation of the problem was determined, objectives, and justification, to identify the theoretical basis of the subject, and operationalization of variables, the methodological framework was developed in which inductive and deductive scientific methods were applied, the type of the research was descriptive-explanatory, the design of the research was field and not experimental, and the type of study was cross-sectional, consequently the population of 32 children is determined, with emphasis on the technique of observation, as instruments the observation guide was applied, then do a statistical analysis of the results obtained from the scene, to finally make an alternative proposal using an activity guide that helped to strengthen the artistic expression as an alternative learning for the development of motor skills of children at the education unit Camilo Gallegos Toledo, after having applied the guide, it was observed that children favorably started as active and participative during the performance of these activities, it is noticed that a considerable percentage have difficulty in manipulating and synchronize their movements, but it can be improved with the proper application of activities described in this research.